Liquid crystal polymer film, laminate including the same, and method for manufacturing the liquid crystal polymer film

JP7639951B2Active Publication Date: 2025-03-05MURATA MFG CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023576093
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-08-03
Filing Date
2023-06-14
Publication Date
2025-03-05
Estimated Expiration
2043-06-14

AI Technical Summary

Benefits of technology

【0009】 本開示によれば、液晶ポリマーフィルム中において無機フィラー同士の距離がある程度確保されている。このため、無機フィラーが局所的に密に存在しない。よって、フィルムの主面の面内方向における液晶ポリマーの分子の配向が無機フィラーによって阻害されることを抑制できる。ひいては、フィルムの主面の面内方向における線膨張係数の上昇を抑制しつつ、無機フィラーの添加により比誘電率の上昇した液晶ポリマーフィルムを提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639951000002
    Figure 0007639951000002
  • Figure 0007639951000003
    Figure 0007639951000003
  • Figure 0007639951000004
    Figure 0007639951000004
Patent Text Reader

Abstract

A liquid crystal polymer film (10) according to the present disclosure contains a liquid crystal polymer (1) and an inorganic filler (2), and has a relative permittivity of 5-10. The average of inter barycenter coordinate distances between particles of the inorganic filler (2) in the liquid crystal polymer film (10) is 0.5-2.0 μm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a liquid crystal polymer film, a laminate including the same, and a method for producing a liquid crystal polymer film. [Background technology]

[0002] JP 2006-233118 A (Patent Document 1) discloses a resin composition for antenna parts, which contains a liquid crystal resin and a ceramic powder. JP 2020-167336 A (Patent Document 2) discloses an element-embedded substrate having an element-forming layer formed in a substrate body made of a liquid crystal polymer and composed of an insulating region having a functional filler for forming elements dispersed therein. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2006-233118 A [Patent Document 2] JP 2020-167336 A Summary of the Invention [Problem to be solved by the invention]

[0004] A liquid crystal polymer film formed by mixing an inorganic filler having a high relative dielectric constant with a liquid crystal polymer has a high relative dielectric constant, and therefore, when a liquid crystal polymer film containing an inorganic filler is used for a high-frequency antenna substrate, the radiation electrode area of ​​the high-frequency antenna substrate can be made sufficiently small.

[0005] Here, the liquid crystal polymer has a small linear expansion coefficient in the orientation direction of the molecules, and a large linear expansion coefficient in the direction perpendicular to the orientation direction. Therefore, in the liquid crystal polymer film, in order to reduce the linear expansion coefficient in the in-plane direction of the main surface of the film, it is preferable that the molecules of the liquid crystal polymer are oriented along the in-plane direction of the main surface of the film. When a flexible copper-clad laminate (FCCL) is manufactured by laminating the liquid crystal polymer film on, for example, a copper foil, if the linear expansion coefficient in the in-plane direction of the main surface of the film is small, warping and distortion of the FCCL caused by the difference in the linear expansion coefficient between the liquid crystal polymer film and the copper plate can be suppressed.

[0006] However, when an inorganic filler is mixed into a liquid crystal polymer, the orientation of the liquid crystal polymer molecules along the in-plane direction of the main surface is disturbed, and the linear expansion coefficient of the liquid crystal polymer film in the in-plane direction of the main surface increases. In an FCCL including such a liquid crystal polymer film, the difference in the linear expansion coefficient between the liquid crystal polymer film and the copper foil in the in-plane direction of the main surface of the FCCL increases, causing warping and distortion of the FCCL.

[0007] The present disclosure has been made in consideration of the above problems, and aims to provide a liquid crystal polymer film in which the dielectric constant is increased by adding an inorganic filler while suppressing an increase in the linear expansion coefficient in the in-plane direction of the main surface of the film. [Means for solving the problem]

[0008] A liquid crystal polymer film according to the present disclosure includes a liquid crystal polymer and an inorganic filler. The liquid crystal polymer film has a relative dielectric constant of 5 to 10. The average distance between the center of gravity coordinates of the inorganic filler particles in the liquid crystal polymer film is 0.5 μm to 2.0 μm. Effect of the Invention

[0009] According to the present disclosure, the distance between inorganic fillers is secured to a certain degree in the liquid crystal polymer film. Therefore, the inorganic filler is not locally densely present. Therefore, it is possible to suppress the molecular orientation of the liquid crystal polymer in the in-plane direction of the main surface of the film from being hindered by the inorganic filler. In addition, it is possible to provide a liquid crystal polymer film in which the relative dielectric constant is increased by adding the inorganic filler while suppressing the increase in the linear expansion coefficient in the in-plane direction of the main surface of the film. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view of a laminate according to an embodiment of the present disclosure. [Diagram 2] 1 is an image showing an example of a photograph of a cross section of an LCP film according to one embodiment of the present disclosure taken using a backscattered electron image from an SEM. [Diagram 3] FIG. 2 is a diagram showing an example of a binarized image obtained by binarizing a captured image of a cross section of an LCP film according to an embodiment of the present disclosure. [Figure 4] FIG. 2 is a diagram illustrating a state in which the average value of the distance between the coordinates of the centers of gravity of inorganic fillers is measured from a binarized image of a cross section of an LCP film according to an embodiment of the present disclosure. [Diagram 5] FIG. 2 is a flow diagram showing a manufacturing process of a liquid crystal polymer film according to an embodiment of the present disclosure. [Figure 6] 1 is a cross-sectional view that illustrates a laminate according to Comparative Example 1. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present disclosure will be described, but the present disclosure is not limited thereto. In the drawings, the same or corresponding parts are denoted by the same reference characters, and the description thereof will not be repeated.

[0012] <Laminate> The laminate according to an embodiment of the present disclosure includes a liquid crystal polymer film (LCP film) and a conductive layer laminated on the liquid crystal polymer film. In the laminate according to an embodiment of the present disclosure, the linear expansion coefficient in the in-plane direction of the main surface of the liquid crystal polymer film is suppressed to be relatively low as described below, so that the difference in the linear expansion coefficient between the liquid crystal polymer film and the conductive layer is relatively small. Therefore, the laminate according to this embodiment has suppressed warping. The amount of warping of the laminate is preferably 10 mm or less. If the amount of warping of the laminate is 10 mm or less, and the conductive layer is copper foil, the laminate can be suitably used as a flexible copper-clad laminate. In this specification, the amount of warping of the laminate is a value obtained by cutting a test piece into a square of 150 mm from the laminate direction, placing the test piece on a reference plane so that the conductive layer is in contact with the reference plane, and then measuring the distance from the reference plane to each of the four corners of the test piece, and averaging the measured values ​​of these four distances.

[0013] As described above, the conductive layer may be, for example, a copper foil made of copper. When the conductive layer is a copper foil, the laminate may be a so-called flexible copper clad laminate (FCCL). The conductive layer may be formed in a circuit pattern. Furthermore, via holes may be formed in the liquid crystal polymer film, and a resin layer and another conductive layer may be further laminated on the conductive layer. In this way, the laminate may be a so-called flexible printed circuit board.

[0014] <Liquid crystal polymer film> A liquid crystal polymer film (LCP film) according to an embodiment of the present disclosure includes a liquid crystal polymer (LCP) and an inorganic filler.

[0015] The liquid crystal polymer film according to an embodiment of the present disclosure has a dielectric constant of 5 or more and 10 or less, as measured by applying a high-frequency signal of 12 GHz at an ambient temperature of 25° C. using a cavity resonator method in accordance with JIS R 1641. If the dielectric constant of the liquid crystal polymer film is less than 5, when the liquid crystal polymer film is used as a high-frequency antenna substrate, the radiation electrode area of ​​the high-frequency antenna substrate cannot be sufficiently reduced. In addition, if the dielectric constant of the liquid crystal polymer film is more than 10, the antenna efficiency is deteriorated.

[0016] Furthermore, the liquid crystal polymer film according to an embodiment of the present disclosure preferably has a dielectric loss tangent of 0.01 or less when measured by applying a high-frequency signal of 30 GHz at an atmospheric temperature of 25° C. using a cavity resonator method in accordance with JIS R 1641. If the dielectric loss tangent of the LCP film is 0.01 or less, deterioration of antenna efficiency can be suppressed when the LCP film is used as a high-frequency antenna substrate.

[0017] (Liquid Crystal Polymer) The liquid crystal polymer is not particularly limited, but examples thereof include thermotropic liquid crystal polymers, etc. Thermotropic liquid crystal polymers are aromatic polyesters synthesized mainly from monomers such as aromatic diols, aromatic dicarboxylic acids, and aromatic hydroxycarboxylic acids, and exhibit liquid crystallinity when melted.

[0018] The molecules of liquid crystal polymers have a negative coefficient of linear expansion (CTE) in the axial direction of the molecular axis and a positive CTE in the radial direction of the molecular axis.

[0019] The liquid crystal polymer is preferably free of amide bonds. Examples of thermotropic liquid crystal polymers free of amide bonds include a copolymer of parahydroxybenzoic acid, terephthalic acid and dihydroxybiphenyl (block copolymer of parahydroxybenzoic acid and ethylene terephthalate) having a high melting point and low CTE, called 1-type liquid crystal polymer, or a copolymer (block copolymer) of parahydroxybenzoic acid and 2,6-hydroxynaphthoic acid having a melting point between 1-type liquid crystal polymer and 2-type liquid crystal polymer, called 1.5-type (or 3-type).

[0020] (Liquid Crystal Polymer Powder) The LCP film according to an embodiment of the present disclosure can be produced by a production method described below using a liquid crystal polymer powder (LCP powder) made of the above-mentioned liquid crystal polymer. The LCP powder contains fibrous particles (liquid crystal polymer fibers: LCP fibers) made of a liquid crystal polymer.

[0021] The LCP fibers contained in the LCP powder are not particularly limited as long as they contain a fibrous portion, which may be linear or may have branches.

[0022] The average diameter of the LCP fibers is 2 μm or less, preferably 1.4 μm or less, and more preferably 1 μm or less. The average diameter of the LCP fibers is, for example, 0.07 μm or more. The smaller the average diameter of the LCP fibers, the less the LCP fibers will ride over each other during the production of the LCP film. This makes it easier for the LCP to be oriented in-plane during the production of the LCP film, and reduces the coefficient of linear expansion (CTE) in the main plane of the LCP film and the amount of warping of the flexible copper clad laminate (FCCL). The average aspect ratio of the LCP fibers is preferably 10 or more and 500 or less, and more preferably 10 or more and 300 or less.

[0023] The average diameter and average aspect ratio of the LCP fibers are measured by the following method. First, LCP powder made of LCP fibers to be measured is dispersed in ethanol to prepare a slurry in which 0.01% by mass of LCP powder is dispersed. At this time, the slurry is prepared so that the water content in the slurry is 1% by mass or less. Then, 5 to 10 μL of this slurry is dropped onto a slide glass, and the slurry on the slide glass is allowed to dry naturally. By allowing the slurry to dry naturally, the LCP powder is arranged on the slide glass.

[0024] Next, a predetermined area of ​​the LCP powder placed on the slide glass is observed with a scanning electron microscope (SEM) to collect 100 or more image data of the particles (LCP fibers) constituting the LCP powder. In collecting the image data, the area is set according to the size of each LCP particle so that the number of image data is 100 or more. In addition, in order to prevent the occurrence of missed image data collection or measurement errors for each LCP particle, the magnification of the SEM is appropriately changed to 500x, 3000x, or 10000x to collect the image data.

[0025] Next, the longitudinal dimension and width dimension of each LCP fiber are measured using the collected image data. For one LCP fiber captured in each image data, the direction of the straight line connecting both ends of the longest path from one end of the fiber through approximately the center of the particle to the opposite end of the fiber is defined as the longitudinal direction. The length of the straight line connecting both ends of the longest path is measured as the longitudinal dimension.

[0026] In addition, the particle size in the direction perpendicular to the longitudinal direction is measured at three different points in the longitudinal direction of each particle of the LCP powder. The average value of the dimensions measured at these three points is defined as the width direction dimension (fiber diameter) per particle of the LCP powder. The average value of the fiber diameters measured for 100 LCP fibers is defined as the average diameter.

[0027] The aspect ratio of the LCP fiber is calculated as the ratio of the longitudinal dimension to the fiber diameter (longitudinal dimension / fiber diameter), and the average of the aspect ratios measured for 100 LCP fibers is taken as the average aspect ratio.

[0028] The fibrous particles may be contained in the LCP powder as aggregates of the fibrous particles.

[0029] In addition, the axial direction of the LCP molecules constituting the fibrous particles tends to coincide with the longitudinal direction of the fibrous particles. This is believed to be because, when an LCP powder is produced, destruction occurs between a plurality of domains formed by bundling the LCP molecules, causing the axial direction of the LCP molecules to be oriented along the longitudinal direction of the fibrous particles.

[0030] In the LCP powder, the content (number ratio) of particles other than fibrous particles (aggregated particles that are not substantially fibrous) is preferably 20% or less. For example, when the LCP powder is placed on a flat surface, particles with a maximum height of 10 μm or less are fibrous particles, and particles with a maximum height of more than 10 μm are aggregate particles.

[0031] The LCP powder preferably has a D50 (average particle size) value of 13 μm or less, as measured by particle size measurement using a particle size distribution measuring device based on a laser diffraction scattering method.

[0032] (Inorganic filler) As the filler raw material (inorganic filler), for example, powder of inorganic oxide such as talc, alumina, silica, alkaline earth metal titanate, carbon powder, ceramic powder, glass powder, etc. can be used. In this embodiment, the inorganic filler is preferably an alkaline earth metal titanate. Since the alkaline earth metal titanate is a ferroelectric, the relative dielectric constant of the liquid crystal polymer film can be effectively increased by adding the alkaline earth metal titanate to the liquid crystal polymer. Examples of the alkaline earth metal titanate include barium titanate (BaTiO3), calcium titanate (CaTiO3), and strontium titanate (SrTiO3). Among these, the inorganic filler is preferably barium titanate. Since barium titanate is a ferroelectric with a particularly high relative dielectric constant, the relative dielectric constant of the liquid crystal polymer film can be more effectively increased. In addition, the inorganic filler is also preferably calcium titanate or strontium titanate. By adding calcium titanate or strontium titanate, the increase in the dielectric loss of the liquid crystal polymer film can be suppressed. The filler raw material may be used alone or in combination of two or more kinds.

[0033] The shape of the filler raw material is not particularly limited, and amorphous fillers, plate-like fillers, granular fillers, etc. can be used. The inorganic filler of the present disclosure preferably contains flat fillers. In addition, the "flat filler" in one embodiment of the present disclosure includes fillers obtained by heating and compressing fillers used as raw materials (hereinafter, sometimes referred to as "filler raw materials"), flat filler raw materials, and fillers obtained by agglomerating spherical or other filler raw materials to form flat aggregates.

[0034] The inorganic filler preferably has a D50 (average particle size) value of 0.5 μm or more and 1.5 μm or less, as measured by particle size measurement using a particle size distribution measuring device by a laser diffraction scattering method. If the average particle size of the inorganic filler is 0.5 μm or more, the contact area between the inorganic filler and the LCP is not too large, so that the generation of voids between the inorganic filler and the LCP is suppressed. As a result, the moldability of the LCP film is improved. In addition, if the average particle size of the inorganic filler is 1.5 μm or less, the generation of unevenness on the main surface of the LCP film caused by the external shape of the inorganic filler is suppressed, so that the moldability of the LCP film is improved.

[0035] In addition, the average particle size of the filler raw material is preferably smaller than the average diameter of the LCP fiber. When a filler is mixed with the LCP, the orientation of the LCP fiber is disturbed, but by doing so, the disturbance of the orientation of the LCP fiber can be suppressed.

[0036] In one embodiment of the present disclosure, the ratio of the content of the inorganic filler to the total content of the liquid crystal polymer and the inorganic filler is preferably 20 vol% or more and 30 vol% or less. When the ratio is 20 vol% or more, the relative dielectric constant of the liquid crystal polymer film due to the inorganic filler can be more effectively increased. In addition, when the ratio is 30 vol% or less, the contact area between the inorganic filler and the LCP is not too large, so that the generation of voids between the inorganic filler and the LCP is suppressed. As a result, the moldability of the LCP film is improved.

[0037] In an embodiment of the present disclosure, the inorganic filler preferably has an average aspect ratio of 3 or more, more preferably 4 or more. If the inorganic filler has an average aspect ratio of 3 or more, the LCP molecules are easily oriented along the in-plane direction of the main surface of the LCP film, so that the CTE in the main surface of the LCP film can be made smaller. The inorganic filler also includes flat shapes such as flaky, scaly, and flake-like. Here, the average aspect ratio of the filler is the average value of the aspect ratios calculated by measuring the major axis and minor axis of a plurality of fillers by the method described later. The major axis represents the diameter in the longest direction of the filler, and the minor axis represents the longest length in the direction perpendicular to the major axis. The aspect ratio of each filler is the ratio of the major axis to the minor axis.

[0038] In addition, the average inclination of the inorganic filler relative to the in-plane direction of the principal surface of the LCP film in one embodiment of the present disclosure is preferably within 15°, and more preferably within 10°. If the average inclination of the filler relative to the in-plane direction of the principal surface of the LCP film is within 15°, the LCP molecules are easily oriented along the in-plane direction of the principal surface of the LCP film, so that the CTE in the principal surface of the LCP film can be made smaller.

[0039] FIG. 1 is a schematic cross-sectional view of a laminate according to an embodiment of the present disclosure. As shown in FIG. 1, in an embodiment of the present disclosure, the average value of the distance between the coordinates of the centers of gravity of the particles of the inorganic filler 2 in the liquid crystal polymer film 10 is 0.5 μm or more and 2.0 μm or less. If the average value of the distance between the coordinates of the centers of gravity is 0.5 μm or more, the distance between the particles of the inorganic filler 2 is secured to a certain degree. Therefore, the inorganic filler 2 does not exist locally and densely. Therefore, the orientation of the molecular axis 1a of the liquid crystal polymer 1 along the in-plane direction D of the main surface of the LCP film 10 can be suppressed from being hindered by the inorganic filler 2. In addition, the increase in the linear expansion coefficient in the in-plane direction D of the main surface of the LCP film 10 can be suppressed. In addition, if the average value of the distance between the coordinates of the centers of gravity is 2.0 μm or less, the effect of increasing the relative dielectric constant by adding the inorganic filler to the LCP film can be sufficiently obtained. In FIG. 1, the liquid crystal polymer film 10 is laminated on the conductive layer 20 in the laminate 100.

[0040] The average aspect ratio of the inorganic filler, the average inclination in the thickness direction of the LCP film, and the average distance between the center of gravity coordinates of the particles in the LCP film can be determined by solidifying the periphery of any cross section of the LCP film or FCCL containing the inorganic filler to be measured with resin, mechanically polishing the cross section, photographing the polished cross section using a backscattered electron image of an SEM, and analyzing the photographed image. Figure 2 is an image showing an example of a photograph of a cross section of an LCP film according to an embodiment of the present disclosure using a backscattered electron image of an SEM. As shown in Figure 2, in the photographed image, the area shown in black is mainly an area showing the presence of LCP1, and the area shown in white is mainly an area showing inorganic filler 2.

[0041] The inorganic filler and LCP (powder) can be identified by binarizing the SEM image using image processing software ("ImageJ") as image analysis software. Here, binarization refers to the process of converting the darkness of each pixel into two values, 1 and 0, using a certain reference value (threshold value).

[0042] Specifically, the SEM image is binarized using image processing software ("ImageJ") to obtain a binarized image for recognizing the filler. Here, the binarization is performed, for example, based on the brightness of the pixels. Although there is no clear value for the brightness threshold in the binarization, it is preferable to adjust the threshold so that the ratio of the bright and dark areas matches the actual volumetric mixture ratio of the LCP powder and the filler. FIG. 3 is a diagram showing an example of a binarized image obtained by binarizing a photographed image of a cross section of an LCP film according to an embodiment of the present disclosure. As shown in FIG. 3, in the binarized image, the bright and dark areas correspond to LCP1 and inorganic filler 2, respectively.

[0043] Based on the binarized image, the long and short diameters of the multiple fillers in the microscope image, the inclination with respect to the thickness direction of the LCP film, and the average value of the distance between the center coordinates of the particles in the LCP film are calculated. Here, the number of fillers to be measured is at least 50 or more, and preferably 100 or more. In addition, it is preferable to perform image analysis in multiple fields of view in the same LCP film or FCCL, but even when performing image analysis in a single field of view, image analysis of 50 or more fillers may be performed as described above, and the average value may be the average aspect ratio and the average inclination with respect to the thickness direction of the LCP film. In the present disclosure, the values ​​measured for 50 or more fillers are the average aspect ratio, average inclination, and average value of the distance between the center coordinates of the particles. The field of view may be, for example, 50 μm vertical × 100 μm horizontal. Note that fillers with an aspect ratio of the long and short diameters of 1.1 or less are considered to be true spheres, with an aspect ratio of 1 and an inclination of 45°.

[0044] Regarding the average aspect ratio of the filler, first, the area of ​​each filler is measured by the following formula (1). Area (μm 2 ) = radius of major axis (μm) × radius of minor axis (μm) × pi... Equation (1) Next, the average of the areas measured for 50 or more fillers is taken as the average area, and the area average ratio of each filler is calculated by the following formula (2). Area average ratio = area (μm2 ) ÷ average area (μm 2 )...Equation (2) The larger the cross-sectional area of ​​the filler, the greater the influence it has on the orientation of more LCP fibers and the greater the effect it has on the CTE. Therefore, the corrected aspect ratio of the filler is calculated using the following formula (3). Corrected aspect ratio = measured aspect ratio × area average ratio (3) In the present disclosure, the average of the above corrected aspect ratios is defined as the average aspect ratio.

[0045] In addition, the larger the cross-sectional area of ​​the filler, the greater the influence it has on the orientation of many LCP fibers and the greater the influence it has on the CTE. Therefore, the correction slope of the filler is calculated using the following formula (4). Corrected inclination (°) = Measured inclination (°) × Area average ratio (4) In the present disclosure, the average of the above corrected slopes is defined as the average slope.

[0046] Regarding the average value of the distance between the coordinates of the centers of gravity of inorganic filler particles in the LCP film, first, the central coordinates (coordinates of the center of gravity) of each inorganic filler particle in the binarized image are calculated. Then, the distance between the central coordinates of a specific inorganic filler particle and the central coordinates of each of the other inorganic filler particles is measured. The smallest distance among the measured distances is set as the distance between the coordinates of the centers of gravity of the one inorganic filler particle. Then, the average value of the distance between the coordinates of the centers of gravity of 50 or more inorganic filler particles that are the measurement object is set as the average value of the distance between the coordinates of the centers of gravity of inorganic fillers in the LCP film. FIG. 4 is a schematic diagram showing a state in which the average value of the distance between the coordinates of the centers of gravity of inorganic fillers is measured from a binarized image of a cross section of an LCP film according to an embodiment of the present disclosure. As shown in FIG. 4, in the binarized image, the distance between the coordinates of the center of gravity of each particle of the inorganic filler 2 to be measured and the other particles is measured.

[0047] (Additives) The liquid crystal polymer film may further contain an additive. Examples of the additive include a dispersant, a leveling agent, a stabilizer, a surfactant, and a silane coupling agent. The liquid crystal polymer film preferably contains, as an additive, a dispersant for dispersing the inorganic filler well in the LCP film, or a silane coupling agent. Examples of the dispersant include an acrylic dispersant. Examples of the silane coupling agent include a methacrylic silane coupling agent. The liquid crystal polymer film may not contain additives such as a dispersant or a silane coupling agent.

[0048] The content of the dispersant or silane coupling agent in the LCP is, for example, preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and even more preferably 0.5% by mass or more, based on the content of the inorganic filler in the LCP film. If the content of the dispersant or silane coupling agent is 0.1% by mass or more based on the content of the inorganic filler, the inorganic filler is well dispersed in the LCP. The upper limit of the content of the dispersant or silane coupling agent in the LCP is not particularly limited. The content of the dispersant or silane coupling agent in the LCP may be, for example, 3% by mass or less based on the content of the inorganic filler in the LCP film.

[0049] <Method of manufacturing liquid crystal polymer film> Each step of the manufacturing method of this embodiment will be described below. 5 is a flow diagram showing a manufacturing process of a liquid crystal polymer film according to an embodiment of the present disclosure. As shown in FIG. 5, the manufacturing method of a liquid crystal polymer film according to this embodiment includes a dispersing step (S1), a matting step (S2), a heat pressing step (S3), and a metal foil removing step (S4).

[0050] First, the method for producing the LCP powder used in the dispersion step (S1) will be described in detail. The LCP powder can be produced, for example, by carrying out the following coarse pulverization step, fine pulverization step, coarse particle removal step, and fiberization step in this order.

[0051] The shape of the raw material (LCP raw material) made of LCP used to prepare the LCP powder can be, for example, uniaxially oriented pellets, biaxially oriented film, powdered LCP, etc. The LCP constituting the LCP raw material is the same as the LCP constituting the above-mentioned LCP fiber.

[0052] (Coarse grinding process) In the coarse pulverization step, the LCP raw material is coarsely pulverized. For example, the LCP raw material is coarsely pulverized with a cutter mill. The size of the coarsely pulverized LCP particles is not particularly limited as long as it can be used as a raw material for the fine pulverization step described later. The maximum particle size of the coarsely pulverized LCP particles is, for example, 3 mm or less.

[0053] It is not always necessary to carry out the coarse pulverization step. For example, if the LCP raw material can be used as a raw material for the fine pulverization step, the LCP raw material may be used directly as a raw material for the fine pulverization step.

[0054] (Fine grinding process) In the fine pulverization step, the LCP raw material (after the coarse pulverization step) is pulverized while being dispersed in liquid nitrogen to obtain granular finely pulverized liquid crystal polymer (finely pulverized LCP).

[0055] In the pulverization step, it is preferable to use media to pulverize the LCP raw material dispersed in liquid nitrogen. The media is, for example, beads. In the pulverization step of this embodiment, it is preferable to use a bead mill, which has relatively few technical problems, from the viewpoint of handling liquid nitrogen. An example of a device that can be used in the pulverization step is the liquid nitrogen bead mill "LNM-08" manufactured by IMEX.

[0056] The granular finely pulverized LCP obtained by the fine pulverization process preferably has a D50 of 50 μm or less as measured by a particle size distribution measuring device using a laser diffraction scattering method, which can prevent the granular finely pulverized LCP from clogging the nozzle in the fiberization process described below.

[0057] (Coarse particle removal process) Next, in the coarse particle removal step, coarse particles are removed from the granular pulverized LCP obtained in the pulverization step. For example, the granular pulverized LCP is sieved with a mesh to obtain granular pulverized LCP that falls below the sieve, and the granular LCP that remains above the sieve is removed to remove the coarse particles contained in the granular pulverized LCP. The type of mesh may be appropriately selected, and an example of the mesh is one with an opening of 53 μm. The coarse particle removal step is not necessarily required.

[0058] (Fiberization process) Next, in the fiberization process, the granular LCP is crushed by a wet high-pressure crushing device to obtain LCP powder. In the fiberization process, the finely pulverized LCP is first dispersed in a dispersion medium for the fiberization process. The finely pulverized LCP to be dispersed does not need to have coarse particles removed, but it is preferable that the coarse particles have been removed. Examples of the dispersion medium for the fiberization process include water, ethanol, methanol, isopropyl alcohol, toluene, benzene, xylene, phenol, acetone, methyl ethyl ketone, diethyl ether, dimethyl ether, hexane, or mixtures thereof.

[0059] Then, the finely pulverized LCP dispersed in the dispersion medium for the fiberization process, i.e., the finely pulverized LCP in a paste or slurry state, is passed through a nozzle under high pressure. By passing through the nozzle under high pressure, the shear force or collision energy due to the high-speed flow in the nozzle acts on the LCP, crushing the granular finely pulverized LCP, and the fiberization of the LCP progresses, and an LCP powder consisting of fine LCP fibers can be obtained. The pressure during the pressurization is, for example, 100 MPa or more and 300 MPa or less. From the viewpoint of applying a high shear force or high collision energy, it is preferable that the nozzle diameter of the nozzle is as small as possible within a range in which the finely pulverized LCP does not clog the nozzle. Since the particle diameter of the granular finely pulverized LCP is relatively small, the nozzle diameter of the wet high-pressure crushing device used in the fiberization process can be made small. The nozzle diameter is, for example, 0.2 mm or less.

[0060] As described above, a plurality of fine cracks are formed in the granular pulverized LCP. Therefore, the dispersion medium penetrates into the inside of the pulverized LCP through the fine cracks by pressurization in the wet high-pressure crushing device. Then, when the paste-like or slurry-like pulverized LCP passes through the nozzle and is placed under normal pressure, the dispersion medium that penetrates into the inside of the pulverized LCP expands in a short time. The dispersion medium that penetrates into the inside of the pulverized LCP expands, and destruction proceeds from the inside of the pulverized LCP. Therefore, fiberization proceeds to the inside of the pulverized LCP, and the LCP molecules are separated into domain units in which they are aligned in one direction. Thus, in the fiberization process in this embodiment, by defibrating the granular pulverized LCP obtained in the fine pulverization process in this embodiment, an LCP powder having a lower content of aggregated particles and consisting of fine LCP fibers can be obtained, compared to the LCP powder obtained by crushing the granular LCP obtained by the conventional freeze-pulverization method.

[0061] In the fiberization step in this embodiment, the finely pulverized LCP may be crushed multiple times with a wet high-pressure crushing device to obtain LCP powder, but from the viewpoint of production efficiency, it is preferable to crush the LCP powder with the wet high-pressure crushing device a small number of times, for example, 5 times or less. Also, from the viewpoint of obtaining LCP powder with a smaller average diameter, it is preferable to crush the LCP powder with the wet high-pressure crushing device a large number of times, for example, 6 times or more and 90 times or less.

[0062] (Dispersion process: S1) In the dispersion step, which is the first step in the method for producing an LCP film, the LCP powder and the filler material are dispersed in a dispersion medium to form a paste or slurry. In this manner, in the present embodiment, since a fine fibrous LCP powder and a filler material with a small average particle size are used, the LCP powder and the filler material can be dispersed in a highly viscous dispersion medium. As a result, a homogeneous LCP film can be produced.

[0063] Examples of the dispersion medium used in the dispersion step include butanediol, water, ethanol, terpineol, a mixture of water and ethanol, etc. For example, when butanediol is used as the dispersion medium, a mixture of the LCP powder and the filler in a paste form is obtained. When a mixture of water and ethanol is used as the dispersion medium, a mixture of the LCP powder and the filler in a slurry form is obtained.

[0064] The mixture of the LCP powder and the filler may further contain additives such as a dispersant and a silane coupling agent, which allows the LCP powder and the filler raw materials to be well dispersed in the mixture.

[0065] The mixing ratio of the LCP powder and the filler raw material may be, for example, 5:5 to 8:2 by volume. If the volume ratio of the filler raw material is greater than that of the LCP powder, the filler becomes the main component in the mixture, making it difficult to form the mixture into a film. It is more preferable to mix the LCP powder and the filler raw material at a volume ratio of 7:3 to 8:2. In other words, it is more preferable to mix the LCP filler and the inorganic filler raw material so that the ratio of the content of the inorganic filler to the total content of the liquid crystal polymer and the inorganic filler in the liquid crystal polymer film is 20 vol% or more and 30 vol% or less. When the ratio is 20 vol% or more, the relative dielectric constant of the liquid crystal polymer film due to the inorganic filler can be more effectively increased. When the ratio is 30 vol% or less, the contact area between the inorganic filler and the LCP does not become too large, so that the generation of voids between the inorganic filler and the LCP is suppressed. As a result, the moldability of the LCP film is improved.

[0066] (Matting process: S2) Next, in the matting process, the mixture of the LCP powder and the filler in the form of a paste or slurry is dried to form a liquid crystal polymer fiber mat (LCP fiber mat). In one embodiment of the present invention, the matting process includes, for example, a coating process and a drying process.

[0067] In the coating process, a mixture of the LCP powder paste and the filler is applied to a metal foil such as a copper foil. In the coating process, the mixture of the LCP powder paste and the filler is applied to a metal foil such as a copper foil as described above, but instead of the metal foil, a polyimide film, a PTFE film, or a composite sheet made of a reinforcing material such as a glass fiber fabric and a heat-resistant resin that does not easily adhere to LCP may be used. This makes it easy to industrially produce the LCP film.

[0068] Next, in the drying process, the mixture of the LCP powder paste and the filler applied to the copper foil is heated and dried to evaporate the dispersion medium. By this heating and drying, an LCP fiber mat is formed on the metal foil such as the copper foil.

[0069] In addition, in the drying process, the dispersion medium is gradually removed from the mixture of the LCP powder paste and the filler, so that the total thickness of the mixture of the LCP powder paste and the filler gradually decreases during drying, and therefore the thickness of the LCP fiber mat becomes thinner than the total thickness of the mixture of the LCP powder paste and the filler formed on the copper foil.

[0070] Furthermore, as the total thickness of the mixture of the paste-like LCP powder and the filler gradually decreases during drying, the longitudinal direction of the fibrous particles in the LCP powder changes. Specifically, among the fibrous particles, the fibrous particles having the longitudinal direction in the total thickness direction of the mixture of the paste-like LCP powder and the filler tilt so that the longitudinal direction faces the in-plane direction of the main surface of the copper foil. Therefore, the longitudinal direction of the fibrous particles in the formed LCP fiber mat is anisotropic.

[0071] In the matting step, a mixture of LCP powder and filler in a paste form may be applied onto the LCP fiber mat formed on the metal foil by the drying step, and then the mixture may be dried to evaporate the dispersion medium. In this manner, the matting step may include a coating step and a drying step repeated in this order. This allows an LCP fiber mat having a desired basis weight to be obtained. In addition, when the coating step and the drying step are repeatedly performed, a mixture in which the mixing ratio of the LCP powder and the filler is changed for each coating step may be used. This allows an LCP fiber mat capable of forming an LCP film having desired properties to be obtained.

[0072] In the matting step in this embodiment, instead of the coating step and drying step, a mixture of the slurry-like LCP powder and the filler may be formed into an LCP fiber mat by a papermaking method. The papermaking method does not require the use of a special dispersion medium (e.g., expensive terpineol) used in the coating step. In addition, the papermaking method allows the dispersion medium used in the dispersion step to be easily recovered and reused. In this way, the papermaking method allows the LCP film to be produced at low cost.

[0073] Specifically, in the mat-making process using the papermaking method, a slurry of LCP powder and a filler are first papered onto a mesh, a nonwoven microporous sheet, or a woven fabric, and then the mixture of the slurry of LCP powder and the filler arranged on the mesh is heated and dried to obtain an LCP fiber mat.

[0074] (Hot pressing process: S3) Next, in the hot pressing step, the LCP fiber mat is hot pressed to obtain an LCP film. Also, by hot pressing the LCP fiber mat, the filler material or the aggregate of the filler material becomes flat, and the filler is oriented so as to have an inclination of 15° or less with respect to the in-plane direction of the main surface of the LCP film. Specifically, in the hot pressing step, the LCP fiber mat is hot pressed together with the copper foil. As a result, the hot pressing step also serves as a step of bonding the LCP film and the copper foil to each other, so that the LCP film with the copper foil bonded thereto can be obtained at low cost. Note that, when heating is performed for a long time in the hot pressing step, it is preferable to hot press the LCP fiber mat in a vacuum.

[0075] Heating in the hot pressing process is performed to bond the LCP fibers together. However, in order to easily flatten the filler raw material or the aggregates of the filler raw material, when the average particle size of the filler raw material exceeds 1 μm, it is preferable to perform hot pressing within a range of ±10° C. of the melting point of the filler raw material. Note that when the average particle size of the filler raw material is 1 μm or less, the orientation of the LCP fibers is not easily disturbed, so there is no restriction on the heating temperature. However, when the LCP fibers are surface-treated with ultraviolet light, and when the filler raw material is plasma-treated, it is preferable that the heating temperature in the hot pressing process is equal to or lower than the melting point of the LCP fibers, from the viewpoint of bonding the LCP fibers and the filler raw material to each other at the interface between them.

[0076] The pressure in the heat press step is preferably 3 MPa or more, more preferably 5 MPa or more, so that the filler raw material becomes flat and the filler is oriented at an inclination of 15° or less with respect to the in-plane direction of the main surface of the LCP film. If the pressure is too high, the LCP resin melts and flows, so the pressure is preferably 10 MPa or less.

[0077] The holding time in the hot pressing step is not particularly limited and may be, for example, 5 seconds or more, or may be 10 seconds or more. In addition, since the filler raw material becomes flatter by holding for a long time, the holding time may be, for example, 3 minutes or more, or may be 5 minutes or more.

[0078] In addition, in the hot pressing process, a composite sheet or the like made of a reinforcing material such as a polyimide film, a PTFE film, or a glass fiber fabric and a heat-resistant resin that does not easily adhere to LCP may be sandwiched between the press used in the hot pressing process and the LCP fiber mat.

[0079] Alternatively, instead of the polyimide film, an additional copper foil may be sandwiched between the press and the LCP fiber mat. In this case, an LCP film with copper foil bonded to both sides can be obtained. The LCP film with copper foil bonded to both sides can be used as a double-sided copper foil FCCL.

[0080] The outer dimensions of the LCP film formed by the hot pressing process in the thickness direction, i.e., the planar dimensions along the film surface, are approximately the same as those of the LCP fiber mat before the hot pressing. Then, by the hot pressing, the fibrous particles of the LCP powder in the LCP fiber mat, which have a longitudinal direction along the thickness direction of the LCP fiber mat, are heated while being pressed down in the in-plane direction of the main surface of the copper foil. Since the LCP constituting the LCP powder has a molecular axial direction in the longitudinal direction of the fibrous particles, the axial direction of the LCP molecules is also pressed down in the in-plane direction of the main surface of the copper foil. Therefore, except for the molecules constituting the agglomerated particles, the axial direction of each of the molecules constituting the LCP is oriented along the in-plane direction of the main surface of the LCP film across the thickness direction of the LCP film. Therefore, in the formed LCP film, the main orientation direction of the LCP molecules tends to be along the in-plane direction of the main surface of the copper foil, i.e., the in-plane direction of the main surface of the LCP film.

[0081] Similarly, the filler is heated while being pressed down in the in-plane direction of the main surface of the copper foil by the hot press, so that the major axis of the filler is oriented in the in-plane direction of the main surface of the LCP film across the thickness direction of the LCP film.

[0082] It is believed that these factors contribute to a reduced CTE within the main surface of the LCP film of this embodiment.

[0083] In addition, when copper foil is laminated to the LCP film, it is possible to reduce the CTE of the LCP film to be approximately the same as the CTE of the copper foil (approximately 18 to 20 ppm / °C), which can suppress defects such as warping due to thermal shrinkage in the LCP film laminated with the copper foil.

[0084] (Metal foil removal process: S4) Finally, if necessary, the metal foil bonded to the LCP film may be removed by etching, etc. This results in a single LCP film with no metal foil bonded thereto. EXAMPLES

[0085] The present disclosure will be described in more detail below by way of examples, but the present disclosure is not limited to these examples.

[0086] <Example 1> (Production of liquid crystal polymer powder) In Example 1, first, uniaxially oriented LCP pellets (cylindrical pellets with a diameter of 3 to 4 mm, melting point: 315° C.) were prepared as the LCP raw material. The LCP material was a block copolymer of parahydroxybenzoic acid and 4,6-hydroxynaphthoic acid.

[0087] This LCP raw material was coarsely pulverized using a cutter mill (MF10 manufactured by IKA). The coarsely pulverized LCP was passed through a 3 mm diameter mesh provided at the outlet of the cutter mill to obtain coarsely pulverized LCP.

[0088] Next, the coarsely pulverized LCP was finely pulverized in a liquid nitrogen bead mill (LNM-08, manufactured by Imex, vessel capacity: 0.8 L). Specifically, 500 mL of media and 30 g of the coarsely pulverized LCP were put into a vessel, and the pulverization process was performed for 120 minutes at a rotation speed of 2000 rpm. Zirconia (ZrO2) beads with a diameter of 5 mm were used as the media. In the liquid nitrogen bead mill, the coarsely pulverized LCP was dispersed in liquid nitrogen and then wet-pulverized. In this way, the coarsely pulverized LCP was pulverized in the liquid nitrogen bead mill to obtain granular finely pulverized LCP. The dispersion liquid obtained by dispersing the finely pulverized LCP in the equine was sieved through a mesh with an opening of 100 μm to remove the coarse particles contained in the finely pulverized LCP, and the finely pulverized LCP that passed through the mesh was collected.

[0089] Next, the finely pulverized LCP from which the coarse particles had been removed was dispersed in a 50% by mass ethanol solution. The ethanol slurry in which the finely pulverized LCP was dispersed was repeatedly crushed five times using a wet high-pressure crushing device under conditions of a nozzle diameter of 0.2 mm and a pressure of 200 MPa, to form fibers. As the wet high-pressure crushing device, a high-pressure dispersing machine (Nano-Veita manufactured by Yoshida Kikai Kogyo Co., Ltd.) was used. The ethanol slurry in which the finely pulverized LCP was dispersed was dried using a spray dryer to obtain an LCP powder. The average fiber diameter (average diameter) measured for 100 LCP fibers contained in the LCP powder was 1.4 μm.

[0090] (Production of liquid crystal polymer films) Barium titanate powder (D50 (average particle size) of 0.5 μm when measured with a laser diffraction particle size distribution analyzer LA-950V2 (manufactured by Horiba, Ltd.)) was prepared as an inorganic filler raw material. This barium titanate powder was dispersed in butanediol so that the concentration was 10% by mass relative to the butanediol, and further, an additive (dispersant: acrylic dispersant) was added to the butanediol in an amount of 1% by mass relative to the barium titanate in the butanediol, and the mixture was stirred using a ball mill to obtain a dispersion of barium titanate.

[0091] The LCP powder was mixed with the dispersion of barium titanate to form a paste. The volume ratio of the LCP powder to the inorganic filler (barium titanate) was 8:2 in the paste mixture.

[0092] Next, the paste-like mixture was applied to the roughened surface of an electrolytic copper foil (FWJ-WS-12, manufactured by Furukawa Electric Co., Ltd.) measuring 180 mm square and 12 μm thick, using a metal plate measuring 160 mm square. The electrolytic copper foil to which the paste-like mixture was applied was heated to 180° C. on a hot plate to vaporize the butanediol dispersion medium, thereby drying the paste-like mixture on the electrolytic copper foil. In this way, a thin LCP fiber mat was formed on the electrolytic copper foil.

[0093] The above paste mixture was further applied onto this thin LCP fiber mat. The applied paste mixture was dried in the same manner as the previously applied paste mixture was dried. In this way, the above application and drying were repeated several times, and the basis weight was increased to 35 g / m2. 2 The LCP fiber mat was formed on an electrolytic copper foil.

[0094] Next, the LCP fiber mat formed on the electrolytic copper foil was hot-pressed together with the electrolytic copper foil using a high-temperature press. Specifically, a release film was first laminated on the side of the LCP fiber mat formed on the electrolytic copper foil opposite to the electrolytic copper foil. A polyimide film (Kapton (registered trademark) 100H, manufactured by Toray DuPont Co., Ltd.) was used as the release film. Then, the LCP fiber mat laminated with the release film was set in the high-temperature press. The set LCP fiber mat was pressed together with the release film and the electrolytic copper foil at a temperature of 295°C and a press pressure of 6 MPa for 10 seconds. The size of the pressing member used for pressing was 170 mm square. After the hot press, the release film was removed to obtain FCCL.

[0095] Finally, the electrolytic copper foil that was bonded to the LCP film was removed by etching with an aqueous solution of ferric chloride. This resulted in the production of an LCP film. The thickness of the LCP film was 25 μm.

[0096] <Example 2> FCCL and LCP films were produced using the same production process as in Example 1, except that a methacrylic silane coupling agent was used as an additive to the barium titanate dispersion, and an ultrasonic agitator was used instead of a ball mill to agitate the barium titanate dispersion.

[0097] <Example 3> FCCL and LCP films were manufactured using the same manufacturing process as in Example 1, except that barium titanate particles having a D50 (average particle size) of 1.2 μm as measured with a laser diffraction particle size distribution analyzer LA-950V2 (manufactured by Horiba, Ltd.) were used.

[0098] <Example 4> FCCL and LCP films were manufactured using the same manufacturing process as in Example 1, except that calcium titanate powder (D50 (average particle size) of 1.5 μm as measured with a laser diffraction particle size distribution analyzer LA-950V2 (manufactured by Horiba, Ltd.)) was used as the inorganic filler raw material instead of barium titanate powder.

[0099] <Example 5> FCCL and LCP films were produced using the same production process as in Example 4, except that a paste-like mixture was prepared so that the volume ratio of the LCP powder to the inorganic filler (calcium titanate) was 7:3.

[0100] <Example 6> In the production of the LCP powder, the ethanol slurry in which the finely pulverized LCP was dispersed was repeatedly crushed 30 times using a wet high-pressure crusher, and the other steps were the same as those used in Example 1 to produce the FCCL and LCP film. The average fiber diameter (average diameter) measured for 100 LCP fibers contained in the LCP powder was 0.8 μm.

[0101] <Comparative Example 1> FCCL and LCP films were produced in the same manner as in Example 1, except that no additive was added to butanediol during preparation of the barium titanate dispersion.

[0102] <Comparative Example 2> FCCL and LCP films were produced using the same production process as in Example 4, except that a paste-like mixture was prepared so that the volume ratio of the LCP powder to the inorganic filler (calcium titanate) was 9:1.

[0103] [Measurement of the average distance between the center of gravity coordinates of inorganic filler particles] The average value of the distance between the coordinates of the centers of gravity of inorganic filler particles in the LCP films according to Examples 1 to 5 and Comparative Examples 1 and 2 was measured by the above-mentioned measurement method. The average value of the distance between the coordinates of the centers of gravity of inorganic filler particles was calculated for 101 particles in Example 1, 134 particles in Example 2, 72 particles in Example 3, 91 particles in Example 4, 105 particles in Example 5, 142 particles in Example 6, 89 particles in Comparative Example 1, and 107 particles in Comparative Example 2.

[0104] [Measurement of linear expansion coefficient] The coefficient of linear expansion (CTE) in the in-plane direction of the main surface was measured for each of the LCP films according to Examples 1 to 6 and Comparative Examples 1 and 2. Specifically, the CTE in the main surface (XY direction) of the LCP film was measured by a TMA (thermo-mechanical analysis) method in accordance with JIS K 7197. The TMA conditions were as follows: using a thermal analyzer (TMA4030SA, manufactured by Bruker), the temperature was raised from room temperature to 150°C in a nitrogen atmosphere, and then cooled to room temperature at a rate of 10°C / min, the load was 10g, and the sample shape was a strip (5mm x 10mm), and the CTE was measured between 80°C and 40°C during the cooling process.

[0105] [Measurement of relative permittivity and dielectric loss tangent] The dielectric constant (Dk) and dielectric loss tangent (Df) were measured for each of the LCP films according to Examples 1 to 6 and Comparative Examples 1 and 2. Specifically, a 30 mm×30 mm test piece (thickness: 50 μm) was prepared for each resin film, and the dielectric constant and dielectric loss tangent of the test piece were measured by a cavity resonator method using a dielectric constant measuring device conforming to JIS R 1641. The measurement was performed by applying a high-frequency signal of 12 GHz at an ambient temperature of 25° C.

[0106] [Calculation of filler volume filling rate] The volumetric filling rate of the inorganic filler in the LCP film was calculated for each of the LCP films according to Examples 1 to 6 and Comparative Examples 1 and 2. Specifically, first, a test piece of 5 cm square was cut out from the LCP film, and the weight of the test piece was measured by an electronic balance to calculate the density of the LCP film. Then, the density of the LCP film was calculated based on the calculated density of the LCP film and the density values ​​of the LCP and each inorganic filler. The density values ​​of the LCP and each inorganic filler may be values ​​previously measured by a pycnometer, or may be values ​​from literature such as "Chemical Handbook (edited by the Chemical Society of Japan, published by Maruzen Publishing)". As a result of the above calculation of the filler volumetric filling rate, it was confirmed that the filler volumetric filling rate in each of the Examples and Comparative Examples was equivalent to the filler volumetric filling rate calculated from the volume ratio of the LCP powder and the inorganic filler (barium titanate) when mixed in the LCP film manufacturing process.

[0107] [Measurement of warpage] The amount of warpage was measured for each of the FCCLs according to Examples 1 to 6 and Comparative Examples 1 and 2. Specifically, a 150 mm square FCCL was placed on a glass plate with the copper foil side facing down, and the distances from the corners of the FCCL to the glass plate were measured, and the average value was taken as the amount of warpage. Note that when the FCCL warps too much, it becomes cylindrical, and the distances from the corners to the glass plate cannot be measured. When the FCCL becomes cylindrical with a circumference of 150 mm, the distance of the corners from the glass plate is at a maximum value (about 48 mm), so the cylindrical shape was taken as ">48 mm".

[0108] The evaluation results for the LCP films and FCCL of each of Examples 1 to 6 and Comparative Examples 1 and 2 are shown in Table 1. [Table 1]

[0109] As shown in Table 1, in Examples 1 to 6 in which the average value of the distance between the coordinate centers of gravity of inorganic filler particles in the LCP film is 0.5 μm or more and 2.0 μm or less, the coefficient of linear expansion (CTE) in the in-plane direction of the main surface of the LCP film is smaller than that of the LCP film of Comparative Example 1 in which the average value of the distance between the coordinate centers of gravity is less than 0.5 μm, and therefore the warpage of the FCCL is smaller. Also, as shown in Table 1, in Examples 1 to 6, the relative dielectric constant (Dk) is higher than that of Comparative Example 2 in which the average value of the distance between the coordinate centers of gravity of inorganic filler particles is more than 2.0 μm.

[0110] Fig. 6 is a cross-sectional view that shows a schematic diagram of a laminate according to Comparative Example 1. As shown in Fig. 6, in the liquid crystal polymer film 90 according to Comparative Example 1, since the average value of the distance between the coordinates of the centers of gravity is less than 0.5 µm, the distance between the particles of the inorganic filler 2 cannot be sufficiently ensured, and it is considered that the molecular axis 1a of the liquid crystal polymer 1 located between the inorganic filler 2 is prevented from being oriented along the in-plane direction D of the main surface of the film.

[0111] Thus, the liquid crystal polymer film according to one embodiment of the present disclosure is a liquid crystal polymer film containing a liquid crystal polymer and an inorganic filler, and has a relative dielectric constant of 5 to 10, and the average value of the distance between the coordinates of the centers of gravity of the particles of the inorganic filler in the liquid crystal polymer film is 0.5 μm to 2.0 μm. According to the above configuration, the distance between the inorganic fillers in the liquid crystal polymer film is secured to a certain degree. Therefore, the inorganic filler is not locally densely present. Therefore, it is possible to suppress the molecular orientation of the liquid crystal polymer in the in-plane direction of the main surface of the film from being hindered by the inorganic filler. In addition, it is possible to provide a liquid crystal polymer film in which the relative dielectric constant is increased by adding the inorganic filler while suppressing the increase in the linear expansion coefficient in the in-plane direction of the main surface of the film.

[0112] [Note] As described above, the present embodiment includes the following disclosure.

[0113] <1> A liquid crystal polymer film comprising a liquid crystal polymer and an inorganic filler, The dielectric constant is 5 or more and 10 or less, A liquid crystal polymer film, wherein an average value of a distance between the coordinates of centers of gravity of particles of the inorganic filler in the liquid crystal polymer film is 0.5 μm or more and 2.0 μm or less.

[0114] <2> The inorganic filler is an alkaline earth metal titanate. <1> The liquid crystal polymer film according to claim 1.

[0115] <3> The inorganic filler is barium titanate. <2> The liquid crystal polymer film according to claim 1.

[0116] <4> The inorganic filler is calcium titanate or strontium titanate. <2> The liquid crystal polymer film according to claim 1.

[0117] <5> The ratio of the content of the inorganic filler to the total content of the liquid crystal polymer and the inorganic filler is 20 vol% or more and 30 vol% or less; <1> from <4> 13. The liquid crystal polymer film according to claim 12 .

[0118] <6> The average particle size of the inorganic filler is 0.5 μm or more and 1.5 μm or less. <1> from <5> 13. The liquid crystal polymer film according to claim 12 .

[0119] <7> <1> from <6> The liquid crystal polymer film according to any one of the above items, and a conductive layer laminated on the liquid crystal polymer film.

[0120] <8> The conductive layer is a copper foil, The amount of warping is 10mm or less. <7> The laminate according to claim 1.

[0121] <9> <1> from <6> The method for producing the liquid crystal polymer film according to any one of the above, A dispersing step of dispersing the liquid crystal polymer powder and the inorganic filler in a dispersion medium to obtain a paste-like or slurry-like mixture; a matting step of drying the paste or slurry mixture to form a mixture mat; and a hot pressing step of hot pressing the mixture mat to obtain the liquid crystal polymer film.

[0122] <10> The liquid crystal polymer powder contains liquid crystal polymer fibers, which are fibrous particles made of the liquid crystal polymer, The average diameter of the liquid crystal polymer fibers is 1.4 μm or less. <9> 2. A method for producing the liquid crystal polymer film according to claim 1 .

[0123] In the above description of the embodiments, configurations that can be combined may be combined with each other.

[0124] The embodiments and examples disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims. [Explanation of symbols]

[0125] 1 liquid crystal polymer, 1a molecular axis, 2 inorganic filler, 10,90 liquid crystal polymer film, 20 conductive layer, 100 laminate.

Claims

1. A liquid crystal polymer film comprising a liquid crystal polymer and an inorganic filler, The dielectric constant is 5 or more and 10 or less, A liquid crystal polymer film, wherein an average value of a distance between the coordinates of centers of gravity of particles of the inorganic filler in the liquid crystal polymer film is 0.5 μm or more and 2.0 μm or less.

2. 2. The liquid crystal polymer film of claim 1, wherein the inorganic filler is an alkaline earth metal titanate.

3. The liquid crystal polymer film of claim 2 , wherein the inorganic filler is barium titanate.

4. The liquid crystal polymer film according to claim 2 , wherein the inorganic filler is calcium titanate or strontium titanate.

5. 2. The liquid crystal polymer film according to claim 1, wherein a ratio of a content of the inorganic filler to a total content of the liquid crystal polymer and the inorganic filler is 20 vol % or more and 30 vol % or less.

6. The liquid crystal polymer film according to claim 1 , wherein the inorganic filler has an average particle size of 0.5 μm or more and 1.5 μm or less.

7. The liquid crystal polymer film according to any one of claims 1 to 6, and a conductive layer laminated on the liquid crystal polymer film.

8. The conductive layer is a copper foil, The laminate according to claim 7, having a warpage of 10 mm or less.

9. A method for producing the liquid crystal polymer film according to any one of claims 1 to 6, comprising the steps of: A dispersing step of dispersing the liquid crystal polymer powder and the inorganic filler in a dispersion medium to obtain a paste-like or slurry-like mixture; a matting step of drying the paste or slurry mixture to form a mixture mat; and a hot pressing step of hot pressing the mixture mat to obtain the liquid crystal polymer film.

10. The liquid crystal polymer powder contains liquid crystal polymer fibers, which are fibrous particles made of the liquid crystal polymer, The method for producing a liquid crystal polymer film according to claim 9, wherein the liquid crystal polymer fibers have an average diameter of 1.4 μm or less.

Citation Information

Patent Citations

  • Packing contained composite material, sheet and circuit board containing same

    CN106928660A

  • Susceptor for microwave oven

    JP1989311172A

  • Resin composition for electronic part

    JP1996041247A

  • Thermoplastic resin composition and molding

    JP2003342431A

  • Thermoplastic resin composition and molded article

    JP2003342478A